# Sine Rule Derivation In Record Time… $\frac { 1 }{ 2 } bc\sin { A } =\frac { 1 }{ 2 } ac\sin { B } \\ \\ \frac { 2 }{ c\sin { A\sin { B } } } \cdot \frac { 1 }{ 2 } bc\sin { A } =\frac { 2 }{ c\sin { A\sin { B } } } \cdot \frac { 1 }{ 2 } ac\sin { B } \\ \\ \frac { 2bc\sin { A } }{ 2c\sin { A\sin { B } } } =\frac { 2ac\sin { B } }{ 2c\sin { A\sin { B } } } \\ \\ \frac { 2 }{ 2 } \cdot \frac { c }{ c } \cdot \frac { \sin { A } }{ \sin { A } } \cdot \frac { b }{ \sin { B } } =\frac { 2 }{ 2 } \cdot \frac { c }{ c } \cdot \frac { \sin { B } }{ \sin { B } } \cdot \frac { a }{ \sin { A } } \\ \\ \frac { b }{ \sin { B } } =\frac { a }{ \sin { A } }$

Now: $\sin { C } =\sin { \left( 90-B+\left( 90-A \right) \right) } \\ \\ \sin { C } =\sin { \left( 180-\left( A+B \right) \right) } \\ \\ \sin { C } =\sin { 180 } \cos { \left( A+B \right) -\cos { 180 } } \sin { \left( A+B \right) } \\ \\ \sin { C } =-\left( -1 \right) \sin { \left( A+B \right) } \\ \\ \sin { C= } \sin { \left( A+B \right) } \\ \\ \sin { C } =\sin { A } \cos { B } +\cos { A } \sin { B } \\ \\ \sin { C= } \frac { 2A }{ bc } \cdot \frac { x }{ a } +\frac { \left( c-x \right) }{ b } \cdot \frac { 2A }{ ac } \\ \\ \sin { C } =\frac { 2Ax }{ acb } +\frac { 2A\left( c-x \right) }{ acb }$ $\\ \\ \sin { C } =\frac { 2Ax+2A\left( c-x \right) }{ acb } \\ \\ \sin { C } =\frac { 2A\left\{ x+\left( c-x \right) \right\} }{ acb } \\ \\ \sin { C= } \frac { 2Ac }{ acb } \\ \\ \frac { ab }{ 2 } \cdot \sin { C } =\frac { 2A }{ ab } \cdot \frac { ab }{ 2 } \\ \\ \frac { 1 }{ 2 } ab\sin { C } =A\\ \\ \therefore \quad \frac { 1 }{ 2 } ab\sin { C } =\frac { 1 }{ 2 } bc\sin { A } \\ \\ \frac { 2 }{ b\sin { A\sin { C } } } \cdot \frac { 1 }{ 2 } ab\sin { C } =\frac { 2 }{ b\sin { A\sin { C } } } \cdot \frac { 1 }{ 2 } bc\sin { A } \\ \\ \frac { a }{ \sin { A } } =\frac { c }{ \sin { C } } \\ \\ \therefore \quad \frac { a }{ \sin { A } } =\frac { b }{ \sin { B } } =\frac { c }{ \sin { C } }$